Education Development in Terms of Digitalization - Lyakhova, Natalia I. (International Journal of Criminology and Sociology, 2022)
The formation of a knowledge society and the digital stage of development of modern civilization culture still remains a continuing process, which itself is experiencing serious internal contradictions and problems. The article discusses the analysis results of digital literacy development among Russians, as one of the most essential areas of the emerging digital economy. The study of statistical and analytical material made it possible to draw the conclusion about the insufficient current level of digital economy competencies in Russia, the need to educate Internet users in information selection, instilling the need for self-development, self-education, developing the skills in useful information selection, and wider introduction of distance technologies in education. In this work, we used the abstract logical general scientific method of cognition and the method of empirical generalization. This approach to the study of the digital economy development allows us to identify the main factors of this process intensification.